2006
DOI: 10.1016/j.amjhyper.2006.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Progression of Abdominal Obesity Are Predictors of Future High Blood Pressure and Hypertension

Abstract: Abdominal obesity and its progression are predictors of future BP and hypertension incidence, independent of the effects of general obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 25 publications
5
52
1
1
Order By: Relevance
“…In this study, we found that waist gain is associated with most MetS parameters, mainly with high levels of TGs and reduced levels of HDL-C and increased BP, as markedly observed in the literature (Carr et al, 2004;Grievink et al, 2004;Chuang et al, 2006;Menke et al, 2007;Hirani et al, 2008). On the other hand, in this study, entering FBS as a variable into analysis did not show any significant relationship with waist gain in both genders, as observed in some studies (Palaniappan et al, 2004;Stolk et al, 2005), possibly indicating a lower interference of waist gain in increases in FBS; however, some other studies showed inconsistent results (Nyamdorj et al, 2009;Sone et al, 2009).…”
supporting
confidence: 61%
“…In this study, we found that waist gain is associated with most MetS parameters, mainly with high levels of TGs and reduced levels of HDL-C and increased BP, as markedly observed in the literature (Carr et al, 2004;Grievink et al, 2004;Chuang et al, 2006;Menke et al, 2007;Hirani et al, 2008). On the other hand, in this study, entering FBS as a variable into analysis did not show any significant relationship with waist gain in both genders, as observed in some studies (Palaniappan et al, 2004;Stolk et al, 2005), possibly indicating a lower interference of waist gain in increases in FBS; however, some other studies showed inconsistent results (Nyamdorj et al, 2009;Sone et al, 2009).…”
supporting
confidence: 61%
“…Further, an increase in physical activity had beneficial effects in our study. The only other report that we have found on the effects of waist circumference change on cardiometabolic risk factors is a 10-year study of Chinese adults (13). Both waist and BMI change, together, were related to change in systolic blood pressure and hypertension.…”
Section: Research Design and Methods -From The Data From An Epidemiolmentioning
confidence: 94%
“…In cross-sectional studies, both are related with risk factors for these diseases (9 -12), but there are few publications on the effects of changes in abdominal adiposity (13). We characterized men and women who gained and lost abdominal adiposity over 9 years and describe the incidence and the improvement in cardiometabolic risk factors according to changes in waist circumference.…”
mentioning
confidence: 99%
“…CTRP1 may represent one of the serum factors produced by adipose tissue that share overlapping functions with adiponectin [5]. Hypertension frequently coexists with metabolic disturbances including glucose intolerance, insulin resistance, abdominal obesity, and dyslipidemia and is defined as one of the components of metabolic syndrome [6].…”
Section: Introductionmentioning
confidence: 99%